Phytochemical Properties of Some Mulberry Genotypes Grown in Malatya Province - Rukiye YAMAN (Yüzüncü Yil Üniversitesi Tarim Bilimleri Dergisi, 2021)
Mulberry fruits contain large amounts of anthocyanins, polyphenols, flavonoids components and minerals which are important for human health. In this study, phytochemical properties of some mulberry genotypes in theecologicalconditions of the Malatya region were investigated. ‘Kenmochi’, ‘Bursa Siyah’, ‘44 BA 05’, ‘Elazığ İçme’, ‘23 MRK 09’ the mulberry genotypes and one patented ‘Ichinose’ cultivar were studied concerning their total phenolic content, total monomeric anthocyanin, total antioxidant capacities and individual sugar compositions. Some mulberry genotypes were found the richest with regard to total phenolic and total anthocyanins content. The total phenolic content was found from 958.60 to 3573.79 mg/kg gallic acid equivalents, total anthocyanin content to vary from 177.10 to 2221.60 mg/kg cyanidin-3-glucoside. The antioxidant activities of ʽKenmochiʼ and ʽ44 BA 05ʼ genotypes were higher than those of the others genotypes. These results will be useful for selecting mulberry species that are important in terms of phytochemical content.